Osteoarthritis: Mechanisms and Therapeutic Advances - Wei Liu; Ning‐Yi Guo; Jian‐Quan Wang; Bing‐Bing Xu (MedComm)
ABSTRACT Osteoarthritis (OA) is a chronic joint disease characterized by a complex pathological mechanism, including chondrocyte dysfunction, synovial inflammation, subchondral bone remodeling, and molecular regulation abnormalities. Key signaling pathways such as nuclear factor‐κB, mitoase‐activated protein kinase, and transforming growth factor‐β are disrupted, leading to cytokine imbalance, oxidative stress, and excessive protease activity, which collectively contribute to cartilage degeneration. This review summarizes the potential causes of OA, focusing on cellular and structural abnormalities in cartilage, synovial tissue, and subchondral bone, as well as dysregulation of signaling pathways, gene regulation, and molecular mechanisms. Given the limitations of current diagnostic methods for OA, biomarkers may offer new hope. Emerging therapeutic strategies for OA include biologics, intelligent drug delivery, and tissue engineering, aiming to modulate the immune microenvironment while promoting cartilage repair. However, these approaches face challenges such as long‐term safety and scalability. Future research may require deeper multidisciplinary collaboration and combination therapies to revolutionize the management of OA and improve patient outcomes.